An Analysıs of Learnıng Englısh Vocabulary for Hearıng Impaıred Student at Dharma Bhaktı Dharma Pertıwı Specıal School 2017/2018 - Puri, Indah Retno; Rodiatun, Rodiatun; Susanto, Susanto (Journal of English Education Studies, 2019)
This study aimed to discover the hearing impaired students’ techniques in learning English vocabulary. The hearing impaired students learned mostly differently with normal people in acquiring meaning of words. The data were acquired qualitatively. The instruments used was observation and interview at the tenth grade of hearing impaired students at Dharma Bhakti Dharma Pertiwi Special School. The result showed the various techniques used by the hearing impaired students. in conclusion, the techniques used by the students was totally different for each students depending on the rest of their hearing sense.